Role of baseline Ga-68-PSMA PET/CT-derived whole-body volumetric parameters in predicting survival outcomes of metastatic castration-resistant prostate cancer patients receiving first-line treatment - AKIN TELLİ, TUĞBA; ÖZGÜVEN, SALİH; FİLİZOĞLU, NUH; ÖZTÜRK, MEHMET SAADEDDİN; ARIKAN, RUKİYE; DEMİRCAN, NAZIM CAN; BAŞOĞLU TÜYLÜ, TUĞBA; ALSAN ÇETİN, İLKNUR; ÖNEŞ, TUNÇ; DANE, FAYSAL; YUMUK, PERRAN FULDEN (My University, 2022)
Objective We aimed to evaluate whether baseline Ga-68-PSMA PET/CT-derived whole-body volumetric parameters could be used as predictive biomarkers for survival in metastatic castration-resistant prostate cancer (mCRPC) patients receiving first-line treatment. Materials and methods This retrospective study included 54 mCRPC patients, who underwent baseline Ga-68-PSMA PET/CT imaging within 1 month before starting first-line treatment. Pre-treatment prostate-specific antigen (PSA) levels and treatments were recorded. SUVmax, SUVmean, whole-body PSMA-derived tumor volume (wbPSMA-TV), and whole-body total lesion PSMA (wbTL-PSMA) were calculated for all patients. PSA response was defined as a decline of >= 50% from pre-treatment value at 12 weeks. Overall survival (OS) was measured from the start of the first-line treatment for mCRPC. Results Docetaxel and abiraterone/enzalutamide were administered to 32 and 22 patients in the first-line setting, respectively. wbPSMA-TV (rho = 0.582, p = 0.004) and wbTL-PSMA (rho = 0.564, p = 0.007) showed moderate positive correlations with PSA levels. Older age (p = 0.02), higher wbPSMA-TV (p = 0.007), higher PSA (p = 0.01), higher number of bone metastases (p = 0.02), and lack of PSA response (p = 0.03) were significantly associated with an increased risk of mortality. Multivariate analysis determined wbPSMA-TV (HR: 1.003, 95% CI 1.001-1.004, p = 0.001) and PSA response (HR: 2.241, 95% CI 1.189-4.222, p = 0.01) as independent predictors of OS. Conclusion The wbPSMA-TV may be a useful tool to reflect tumor burden and predict survival outcomes in patients with mCRPC.
Keywords: Tıp; Dahili Tıp Bilimleri; Nükleer Tıp; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Nuclear medicine; Health Sciences; RADYOLOJİ, NÜKLEER TIP ve MEDİKAL GÖRÜNTÜLEME; Klinik Tıp; Klinik Tıp (MED); RADIOLOGY, NUCLEAR MEDICINE & MEDICAL IMAGING; CLINICAL MEDICINE; Clinical Medicine (MED); Radyoloji ve Ultrason Teknolojisi; Radyoloji, Nükleer Tıp ve Görüntüleme; Radiological and Ultrasound Technology; Radiology, Nuclear Medicine and Imaging; Ga-PSMA PET/CT · Metastatic castration-resistant prostate cancer · Survival · Whole-body volumetric parameters